Leveraging Risk Management and Standardization to Foster Innovation in the Post-Pandemic COVID Era - Prasetya, Bambang; Yopi; Tampubolon, Biatna Dulbert (New Advances in Business, Management and Economics Vol. 5, 2025)
COVID-19, which emerged in late 2019, has profoundly disrupted multiple facets of life, including social, economic, and work models in organizations such as government organizations, private organizations, and businesses. These disruptions have posed significant challenges to global and local supply chains, affecting key activities such as production, processing, distribution, and consumption. Organizations and policymakers have implemented various measures to mitigate the adverse effects of the pandemic, not only to control the health crisis itself but also to address its short-term, mid-term, and long-term socio-economic consequences. On the other hand, there are also opportunities to open innovation based on the lessons learned from the COVID-19 pandemic and offering valuable lessons for organizations and industries to rethink their operational models. The crisis has highlighted the critical role of risk management and standardization in fostering adaptive and resilient systems that can withstand future disruptions. By leveraging structured risk assessment frameworks and standardized practices, organizations can enhance their ability to innovate while maintaining stability and efficiency. This paper describes the role of risk management and standardization in supporting innovation in the new normal based on lessons learned during the COVID-19 pandemic which is the intersection of risk management, standardization, and innovation in the post-pandemic era, emphasizing how structured frameworks can facilitate adaptive solutions. Key factors affecting risk management and standardization on the innovation are identified and analyzed. Some recommendations for improvement based on risk management and standardization are also summarized. The method used in this review is descriptive-analytic based on literature studies from several scientific journals, and publications released by international organizations, associations, and government.